FKBP51, AmotL2 and IQGAP1 Involvement in Cilastatin Prevention of Cisplatin-Induced Tubular Nephrotoxicity in Rats - Rebeca González-Fernández (Cells, 2022)
The immunophilin FKBP51, the angiomotin AmotL2, and the scaffoldin IQGAP1 are overexpressed in many types of cancer, with the highest increase in leucocytes from patients undergoing oxaliplatin chemotherapy. Inflammation is involved in the pathogenesis of nephrotoxicity induced by platinum analogs. Cilastatin prevents renal damage caused by cisplatin. This functional and confocal microscopy study shows the renal focal-segmental expression of TNFα after cisplatin administration in rats, predominantly of tubular localization and mostly prevented by co-administration of cilastatin. FKBP51, AmotL2 and IQGAP1 protein expression increases slightly with cilastatin administration and to a much higher extent with cisplatin, in a cellular- and subcellular-specific manner. Kidney tubule cells expressing FKBP51 show either very low or no expression of TNFα, while cells expressing TNFα have low levels of FKBP51. AmotL2 and TNFα seem to colocalize and their expression is increased in tubular cells. IQGAP1 fluorescence increases with cilastatin, cisplatin and joint cilastatin-cisplatin treatment, and does not correlate with TNFα expression or localization. These data suggest a role for FKBP51, AmotL2 and IQGAP1 in cisplatin toxicity in kidney tubules and in the protective effect of cilastatin through inhibition of dehydropeptidase-I.